Dampak Pernikahan Dini Mengacu Pada Pernikahan Formal Dan Informal Untuk Kesehatan Mental Dan Fisik Remaja - Ningsih, Eka Sarofah; Raehan, Raehan; Subani, Natalia Debi; R, Rahmaniyah; Ruagadi, Henry A. (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Factors that cause early marriage among teenagers include arranged marriages carried out by parents who believe in customs that are afraid that their children will become spinsters, committing adultery for Muslims. Another factor is accidents, this happens because the flow of modernization is increasingly rapidly spreading into the social life of every teenager so that usually teenagers who marry at a relatively young age are forced to do so. The purpose of Community Service is to increase knowledge about the impact of early marriage referring to formal or informal marriage for the mental and physical health of teenagers. The method used in Community Service activities is socialization and education of adolescent health through discussions and questions and answers related to reproductive health conditions. The results of community service were obtained based on post-test data showing that knowledge about the impact of early marriage on teenagers was more in the good category, as many as 45 people out of 47 people with a value of 89 from the total respondents. The conclusion is that early marriage can reduce harmony in the family, this is caused by emotions that are still unstable, the turmoil of young blood and immature ways of thinking. And the inability of the husband to meet the economic needs of the family causes deviations in the community environment.